Teacher Professional Development in Technology-Enhanced Learning Environments: Successful Models for Indian Educators to Succeed in Digital Classrooms - Sinha, Sharad (Indian Journal of Educational Technology, 2025)
This paper describes contemporary models of teacher professional development (TPD) in technology-enhanced learning environments in the Indian education sector. With digital adoption in education continuing at a fast rate, particularly post COVID-19 pandemic and introduction of the National Education Policy 2020, there is a pressing need to reframe how teachers develop technological pedagogical content knowledge. Through systematic review of existing literature and case study analysis in diverse Indian learning contexts, this study finds best models and frameworks that facilitate teachers to build digital competence. Effective TPD programs, as mentioned in this study, consist of continuous learning paths, communities of practice with collaborative interaction, contextualisation of technology integration, and reflective practice. The paper presents a comprehensive TPD framework to suit the country-specific socioeconomic and infrastructural challenges of the Indian education system to maintain the global best practices of digital pedagogy. Based on the evidence in this study, this paper presents an integrated technology-based Teacher Professional Development (TPD) framework to address the unique requirements and problems of the Indian education system.